Description and phylogenetic affinities of two new species of Nomadolepis (Eucestoda, Hymenolepididae) from Eastern Palearctic. Issue 5 (October 2015) - Makarikov, Arseny A.; Mel'nikova, Yulia A.; Tkach, Vasyl V.
Abstract: Two new species of hymenolepidid cestodes belonging to the genus Nomadolepis are described from small mammals in western Siberia and the Far East, Russian Federation. Nomadolepis fareasta n. sp. is described from the striped dwarf hamster Cricetulus barabensis in Amurskaya Oblast' and Nomadolepis shiloi n. sp. is described from the Eurasian harvest mouse Micromys minutus from Novosibirskaya Oblast' and Amurskaya Oblast'. Nomadolepis fareasta n. sp. differs from Nomadolepis merionis, Nomadolepis ellobii and N. shiloi n. sp. in having a substantially longer strobila, longer cirrus-sac and wider ovary. Furthermore, N. fareasta n. sp. can be readily distinguished from its congeners by the arrangement of the testes and the number and size of rostellar hooks. Nomadolepis shiloi n. sp. differs from N. merionis, N. ellobii and N. fareasta n. sp. by the number and length of the rostellar hooks, the presence of irregular transverse anastomoses as well as the length of the cirrus-sac and position of the cirrus-sac in relation to the poral ventral osmoregulatory canal. Morphological differentiation of the two new species from morphologically similar Palearctic species of the related genus Rodentolepis (sensu lato) from rodents is also provided. Phylogenetic affinities of Nomadolepis were studied for the first time using partial sequences of the nuclear ribosomal 28S DNA gene. Phylogenetic analysis strongly supported the status of Nomadolepis as a separate genus closest to Pararodentolepis . Graphical abstract: Highlights: Two new species of Nomadolepis are described from rodents in Eastern Palearctic. Differentiation from closely related species is provided. Phylogenetic position of Nomadolepis has been studied using 28S rDNA sequences. Nomadolepis is phylogenetically and morphologically closest to Pararodentolepis . " Rodentolepis clade" still includes paraphyletic genera and needs further revision.